Stress, anxiety, and depression among parents of children with autism spectrum disorder in Oman: a case–control study - Al-Farsi OA (Dove Medical Press, 2016)
Omar A Al-Farsi,1 Yahya M Al-Farsi,1,2 Marwan M Al-Sharbati,3 Samir H Al-Adawi31Department of Family Medicine and Public Health, College of Medicine and Health Sciences, Sultan Qaboos University, Muscat, Sultanate of Oman; 2Department of Epidemiology, School of Public Health, Boston, MA, USA; 3Department of Behavioural Medicine, College of Medicine and Health Sciences, Sultan Qaboos University, Muscat, Sultanate of Oman Abstract: Previous studies carried out in Euro-American populations have unequivocally indicated that psychological disorders of the CASD (caregivers of children with autism spectrum disorder) are marked with high levels of stress, anxiety, and depression. This finding has been attributed to the reaction of having to care for a child with neurodevelopmental disorders. While there have been reports on autism spectrum disorder in Arab/Islamic countries such as Oman, there is no study from this region, to our knowledge, reporting the performance of indices of stress, anxiety, and depression among CASD. This study aimed to examine whether there is variation in the performance of indices of stress, depression, and anxiety explored via Depression, Anxiety and Stress Scale 21 among CASD, caregivers of children with intellectual disabilities, and caregivers of typically developing children. All indices of stress, depression, and anxiety were higher in CASD compared to other caregivers in the control group. This study corroborates with other studies carried out in other populations that caring for children impacts the mental health status of caregivers. Therefore, there are strong grounds to contemplate the mechanism to help such a vulnerable group of family caregivers. Keywords: stress, anxiety, depression, caregivers, autism, Oman